Narrative Analysis of Beauty Standards in Korea: A Study of Sienna Hong's YouTube Content (Sastra Inggris UNPAM, 2024)
This study explores the perspectives and personal experiences of Sienna Hong, a YouTube content creator, on the societal beauty standards prevalent in South Korea. It offers valuable insights into the complex dynamics surrounding these standards and their broader societal implications. Through qualitative data analysis, this research employs Seymour Chatman’s (1978) narrative theory to examine the narrative components that bring these issues to light. The findings reveal an engaging portrayal of Sienna Hong's storytelling, which skillfully balances casual and formal language styles, enhancing the appeal and relatability of her content. This study highlights the importance of narrative elements in digital storytelling, particularly within the context of YouTube vlogs.